2021
DOI: 10.1080/1612197x.2020.1869802
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionistic concerns cognitions predict burnout in college athletes: a three-month longitudinal study

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that certain aspects of perfectionism (e.g., parental criticism and concern over mistakes) are associated with lower self-esteem ( Gotwals et al, 2003 ). Further, athletes who score higher in perfectionism are at higher risk for decreased motivation, which can lead to higher levels of burnout ( Gould, 1996 ; Crowell and Madigan, 2022 ). Thus, high achieving individuals can become emotionally and physically exhausted because they must do something they may no longer feel like doing.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that certain aspects of perfectionism (e.g., parental criticism and concern over mistakes) are associated with lower self-esteem ( Gotwals et al, 2003 ). Further, athletes who score higher in perfectionism are at higher risk for decreased motivation, which can lead to higher levels of burnout ( Gould, 1996 ; Crowell and Madigan, 2022 ). Thus, high achieving individuals can become emotionally and physically exhausted because they must do something they may no longer feel like doing.…”
Section: Introductionmentioning
confidence: 99%